Aktivitas Antioksidan dan Total Polisakarida Ekstrak Rumput Laut Merah, Hijau dan Coklat dari Pantai Jangkar Situbondo - Didin Erma Indahyani; Depi Praharani; Izzata Barid; Ari Tri Wanodyo Handayani (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2019)
The antioxidant activity and polysaccharide composition of seaweed is influenced by species (red, green and brown seaweed), geographical conditions, extraction methods, solvents, temperature and the length of time of extraction. The purpose of this study was to known the total polysaccharide and antioxidant activity in red, green and brown seaweed extracts from Jangkar Situbondo beach. Method. The study was conducted on red, green and brown seaweed extracted with ethanol and water to determine total polysaccharides. Antioxidant analysis uses the method 2,2-diphenyl1-picrylhydrazyl (DPPH) radical. Total polysaccharide and antioxidant activity were observed statistically using two-way ANOVA. The results of this study show that the polysaccharide content in seaweed water extract was significantly higher than ethanol extract, especially in brown seaweed. Seaweed water extracts showed higher antioxidant activity than ethanol extracts. The antioxidant activity of brown seaweed was significantly higher than that of green and red seaweed. Conclusion. Seaweeds have high antioxidant activity in water extracts. Brown seaweed water extract contains high polysaccharides than green and red seaweed. Antioxidant activity in brown seaweed is also higher than in green and red seaweed.